Factorial experimental design for xylanase production by Bacillus sp. isolated from Malaysia landfill soil - Siti Nor Amira, Rosli; Rohaida, Che Man; N., Masngut (IOP Publishing, 2019)
Two-level full factorial design was applied to screen the important parameters for production of xylanase by newly isolated Bacillus sp. from landfill soil. Five production parameters were considered: initial pH media (pH 5–9), inoculum size (5%–10% v/v), incubation period (18–30 h), temperature (30-50 °C) and agitation speed (0-200 rpm). Xylanase activity was estimated using dinitrosalicylic acid (DNS) based on the xylose released under specified assay conditions. Based on the factorial analysis, it was observed that the significant parameters in the xylanase production were temperature, agitation speed and initial pH of media. Meanwhile, the interaction between temperature and initial pH of media gave the highest influenced to the xylanase production. The model revealed that the highest xylanase activity can be achieved at 123.34 U/mL with initial pH media of 7.0, 30 h incubation period, 5% (v/v) inoculum size, agitation speed of 100 rpm at 40 °C. Confirmation run produced the highest experimental xylanase activity by Bacillus sp. at 123.10 U/mL with 0.17% of error than the predicted one. Hence, the model was reliably predicting the xylanase production.